The IT Master Plan Development of Randegan Village - Anita Wulansari; Tri Lathif Mardi Suryanto; Narti Apriyanti; Anindita Pratita; Usmanur Dian Iswanti; Lidya Bela Simarmata; vana Elfirdaus (Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
This research focuses on the transformation of Randegan Village into a Smart Village through the integration of digital technology and community empowerment. The main objective of this research is the implementation of e-government in Randegan Village through the design of an IT Master Plan to achieve a smart village. The research design involved a comprehensive analysis of the Smart Village model and literature review by citing insights from the Smart City concept and successful implementation case studies from past research. To help achieve a smart village in Randegan Village, the research team aims to carry out sensing, understanding, controlling, in Randegan Village so that an IT master plan can be created which then has the potential to become a Smart Village Development Master Plan in Randegan Village. The result is that there is a need for cooperation between educational institutions and the community to increase technological literacy. Technology education programs are suggested to overcome challenges of technology adoption. Community involvement is considered very important in developing technology applications, to encourage their acceptance and benefits. The allocation of resources for technology infrastructure is considered important, and it is also important to work with government to ensure financial support and technical assistance. The results of this study are expected to help Randegan Village in determining policies and programs for developing village information systems so that later they can improve the quality of service to villagers, increasing economic growth, and quality of life in randegan village.